ANALYSIS OF SUITABILITY INDICATORS AND BASIC COMPETENCIES OF ISLAMIC EDUCATION LEARNING BASED ON THE REVISION OF BLOOM'S TAXONOMY - Wisono, Dody; Khozin, Khozin; Temarwut, Taufik (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2023)
The purpose of this study was to describe the suitability of indicators for basic competence in the implementation of learning plans for islamic education subjects at SMK Muhammadiyah Tanjung Redeb based on the revised bloom taxonomy. This research was a qualitative descriptive study. The research location was carried out at the Tanjung Redeb Muhammadiyah Vocational School, Berau Regency, East Kalimantan. The objects in this study were indicators and basic competencies in class XI lesson plans for islamic education which were developed by educators at the Tanjung Redeb Muhammadiyah Vocational School, Berau, East Kalimantan. Data collection techniques used documentation analysis techniques, while for data analysis techniques researchers used interactive techniques Miles, Huberman and Saldana by going through the stages of condensing data, presenting data, and drawing conclusions. As for testing the validity of the data using triangulation. The results of the study showed that there was a discrepancy at the level of basic competence with indicators of achieving competence where these indicators are below basic competence.